Obstacles to open education in our Arab world - Hamada Hamada (Journal of Distance Learning and Open Learning, 2019)
The importance of open education stems from the interest of the Islamic Sharia in education without being restricted to a certain age. This was manifested in the words of the Prophet (peace and blessings of Allah be upon him): "Seek knowledge from the cradle to the grave." Man is required to pursue lifelong learning. It was therefore necessary for the State to provide many forms of education suitable for age, occupation, accommodation, and work. It was the movement from education to learning through the so-called open education that does not require the student to share his teacher in terms of time and place. He is not required to be present throughout the period of study, but can study from his home. Work, age or scientific degrees do not present any obstacles to man's right to complete his education. Many social, cultural, political and other factors made open education and distance education inevitable. The capacity of the traditional universities is not able to absorb this large number of students due to urbanization and the increase in population in all countries of the world in general, and in Arab countries in particular. Therefore, the State had to move from a traditional style that required a student's personal presence at the university to a more flexible system that did not require presence in time or place. The technological advances have progressed rapidly and electronic educational methods have been introduced. This has led to full interaction between the teacher and his student to the point that the teacher can guide his student without the barrier of time or place between them. Therefore, in open education, the teacher's role changed from mere indoctrination to guidance. The learner is instructed teach himself in a self-learning situation. Despite the advantages achieved by open education, there are some obstacles that stand in the way of achieving the objectives of this type of education; so the subject of this research addresses these obstacles and develops solutions to remove them, and sets the mechanism to put these solutions into effect, for open education to achieve full interactivity, and achieve the desired goals and compete traditional education, if not precede it in this regard.